Soybean-Based Cropping System: Dynamics of Crop Straw, Grain Yield, and Soil CO2 Emissions in Conservation Agriculture - Rigon, João Paulo Gonsiorkiewicz; Calonego, Juliano Carlos [UNESP] (Springer Nature, 2025)
The use of cover crops is an essential practice in conservation agriculture, influencing soil carbon dioxide (CO2) emissions and the sustainability of cropping systems in tropical regions. We evaluated soybean grain yield and soil CO2 emissions from crop rotations managed under no-tillage (NT) on a Rhodic Hapludox in tropical conditions from 2013 to 2015. Utilizing a split-plot design, the crop rotations experiment was established in 2006 and repeated annually until 2015. Main plots during the dry fall-winter included Urochloa (Urochloa ruziziensis), Grain sorghum (Sorghum bicolor), and intercropped Urochloa and Sorghum. Subplots in spring consisted of Pearl millet (Pennisetum glaucum), Sunn hemp (Crotolaria juncea), and Forage sorghum (Sorghum bicolor). Soybean (Glycine max) was cropped in summer across the entire area. Soybean yield and soil CO2 emissions varies with crop rotation in atypical summer water deficits. Crop straw inputs in NT crop rotations influence soil CO2 emissions, which increase during spring and soybean seasons and decrease in the dry fall-winter, in line with seasonal temperature and moisture variations. Grain sorghum reduced, while Urochloa increased cumulative soil CO2 emissions; however, when both crops were intercropping in the dry fall-winter, followed by Sunn hemp in the spring, not only reduced soil CO2 emission but also increased the Soybean yield. Intercropping grasses followed by legumes in tropical regions with dry winters presents a more sustainable option for crop rotation under NT. This strategy improves farming efficiency, and part of the carbon losses can be mitigated by increasing the input of crop straw under NT.